Influences of exit examinations on students' choices of learning strategies and resources in the College of Health Sciences and Medicine at Wolaita Sodo University, Ethiopia. - Hankebo, Demissie Dalelo; Koyira, Mengistu Meskel; Naba, Tamene (Humanities & Social Sciences Communications, 2026)
This study investigated the impact of exit exams on learning strategies, students' study behaviors, and the utilization of learning resources among five health science programs: Nursing, Midwifery, Medical Laboratory Science, Public Health, and Pharmacy at Wolaita Sodo University. Data were collected from 170 undergraduate students who took exit exams during the 2023/24 academic year through a survey, open-ended questions and registrar's office documents. The quantitative results showed that exit exams significantly influenced the learning strategies of Medical Laboratory and Midwifery students, while Public Health students experienced the least impact. Nursing students reported the highest level of exam pressure when using learning resources, primarily relying on test blueprints, handouts, and course modules. Thematic analysis revealed that examination stress, time pressure, and anxiety led to surface and strategic approaches to learning, thereby narrowing students' resource utilization and hindering deep learning. Conversely, a few students exhibited resilience and a mastery-oriented approach, highlighting individual differences in coping styles. While there were significant disciplinary differences in students' attitudes towards exit exams, gender did not appear to influence these attitudes. The study found that although exit examinations meet accountability and competency assurance requirements, they inadvertently foster a culture of stress and surface learning. To address these issues, the study recommends implementing discipline-sensitive, competency-based assessment models that incorporate formative assessments and psychosocial support, balancing accountability with student well-being. The College of Health Sciences and Medicine need to establish student support mechanisms, promote diverse assessment methodologies, and enhance access to learning resources to facilitate reflective and collaborative learning. This approach aims to transform exit examinations from high-stakes barriers into opportunities for deep learning, professional development, and lasting educational success. Future research should explore the longitudinal impacts of these exams and evaluate practices across multiple institutions.